Accusations of unbelief in Islam : a diachronic perspective on takfir - Adang, Camilla.; Anṣārī, Ḥasan, 1970 or 1971-; Fierro, Ma. Isabel; Schmidtke, Sabine. (Islamic History and Civilization, 2015)
The present volume-the first of its kind-deals with takfīr : accusing one´s opponents of unbelief ( kufr ). Originating in the first decades of Islam, this practice has been applied intermittently ever since. The nineteen studies included here deal with cases, covering different periods and parts of the Muslim world, of individuals or groups that used the instrument of takfīr to brand their opponents-either persons, groups or even institutions-as unbelievers who should be condemned, anathematized or even persecuted. Each case presented is placed in its sociopolitical and religious context. Together the contributions show the multifariousness that has always characterized Islam and the various ways in which Muslims either sought to suppress or to come to terms with this diversity. With contributions by: Roswitha Badry, Sonja Brentjes, Brian J. Didier, Michael Ebstein, Simeon Evstatiev, Ersilia Francesca, Robert Gleave, Steven Judd, István T. Kristó-Nagy, Göran Larsson, Amalia Levanoni, Orkhan Mir-Kasimov, Hossein Modarressi, Justyna Nedza, Intisar A. Rabb, Sajjad Rizvi, Daniel de Smet, Zoltan Szombathy, Joas Wagemakers.